Creation of the input parameters database for modeling of dynamics of the cloud formed at carrier rocet surface explosion (Journal of Mathematics Mechanics and Computer Science, 2018)
Use of geographic information system (GIS) opportunities is widespread among the experts workingwith large volumes of data. Advantage of GIS in comparison with other information systems isexistence of the digital card giving land surface information. Because of this GIS often use fordynamic processes modeling. In this article the GIS database created for the model of formationand dynamics of the cloud formed at carrier rocet surface explosion is considered. By meansof GIS the model input parameters are collected and systematized, the cartographical basis isprepared. After database integration into the program complex providing model functioning, allinput parameters forms had access to the database. The cartographical basis placed in a primaryinterface window allows to visualize the cloud movement over land surface and his sizes change alsowith the help the map-metric functions to receive the pertinent squares and distances. The additionof the map new "layers"of especially protected natural territories, of a soil cover or infrastructuresubroute territory gives the chance to take additional necessary information. The database is alsostorage for modeling results which will be perhaps used for ecological assessment of cloud influenceon the surrounding environment.
Keywords: Database; geographic information system; carrier rocket accident; modelling; program complex, input parameters